The stress cost of children on moms and dads - Hamermesh, Dan; Wooden, Mark; Buddelmeyer, Hielke (My University, 2018)
We use longitudinal data describing couples in Australia from 2001 to 12 and Germany from 2002 to 12 to examine how demographic events affect mothers’ and fathers’ perceived time and financial stress. Consistent with the view of measures of stress as proxies for Lagrangean multipliers in models of household production, we show that births increase time stress, especially among mothers, and that the effects last at least several years. Births also slightly raise both parents’ financial stress. While the departure of a child from the home reduces parents’ time stress, its negative impacts on the tightness of the time constraints are much smaller than the positive impacts of a birth.
European Economic Review
Keywords: Families and relationships; Income, wealth and finances; International comparison